Visual Transformation of Gender Representation on The Famous Five: Five on a Treasure Island Book Covers (1942-2017) - Imaduddin, Farid; Murtono, Taufik (West Science Social and Humanities Studies, 2025)
This study examines the visual transformation of gender representation on the covers of Enid Blyton's "The Famous Five: Five on a Treasure Island," comparing editions from 1942 and 2017. Using Kress and van Leeuwen's Grammar of Visual Design framework, the research analyzes how visual elements construct gender meaning across different historical contexts. The findings reveal a significant shift in the representation of George (Georgina), from a distinctly masculine-coded character in the 1942 edition to a more feminized portrayal in 2017. Despite being produced in an era of greater gender discourse, the contemporary cover paradoxically presents a less subversive visual model of gender nonconformity. The 1942 illustration depicts George in an active, central position with masculine visual coding that aligns with the character's narrative identity. In contrast, the 2017 cover introduces feminine elements through clothing, posture, and composition that create tension with the character's established rejection of femininity. This transformation reflects complex interactions between changing social norms, commercial considerations, and visual conventions in children's media, demonstrating how design decisions actively participate in constructing cultural understandings of gender.